Imperfect Duties, Group Obligations, and Beneficence - Schroeder, S. Andrew (Journal of moral philosophy, 2014)
There is virtually no philosophical consensus on what, exactly, imperfect duties are. In this paper, I lay out three criteria which I argue any adequate account of imperfect duties should satisfy. Using beneficence as a leading example, I suggest that existing accounts of imperfect duties will have trouble meeting those criteria. I then propose a new approach: thinking of imperfect duties as duties held by groups, rather than individuals. I show, again using the example of beneficence, that this proposal can satisfy the criteria, explaining how something can both have the necessity characteristic of duty, while also allowing agents the latitude which seems to attach to imperfect duties.